2021
DOI: 10.3390/ijerph18158219
|View full text |Cite
|
Sign up to set email alerts
|

Crop Production and Agricultural Carbon Emissions: Relationship Diagnosis and Decomposition Analysis

Abstract: Modern agriculture contributes significantly to greenhouse gas emissions, and agriculture has become the second biggest source of carbon emissions in China. In this context, it is necessary for China to study the nexus of agricultural economic growth and carbon emissions. Taking Jilin province as an example, this paper applied the environmental Kuznets curve (EKC) hypothesis and a decoupling analysis to examine the relationship between crop production and agricultural carbon emissions during 2000–2018, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…According to the EKC hypothesis, the economy-environment relationship follows an inverted U shape: in the process of economic growth, pollutant emissions rise from the beginning, peak in the middle, and fall at the end [2,[13][14][15][16][17][18]. In fact, many EKC studies show that there is also an N shape [19,20], a linear shape [21,22], or even an irregular shape [23,24]. Recently, an increasing number of EKC studies have expanded from traditional pollutant indicators (including atmosphere, water, and land) to new indicators (such as ecological footprint and carbon footprint) [25,26], from indicators of emissions per capita to total emissions [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the EKC hypothesis, the economy-environment relationship follows an inverted U shape: in the process of economic growth, pollutant emissions rise from the beginning, peak in the middle, and fall at the end [2,[13][14][15][16][17][18]. In fact, many EKC studies show that there is also an N shape [19,20], a linear shape [21,22], or even an irregular shape [23,24]. Recently, an increasing number of EKC studies have expanded from traditional pollutant indicators (including atmosphere, water, and land) to new indicators (such as ecological footprint and carbon footprint) [25,26], from indicators of emissions per capita to total emissions [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The carbon emission coefficient of different crop types has certain differences, so the agricultural carbon emission and emission intensity in Hubei Province may also be related to the change of crop planting structure, but this paper does not discuss this problem [ 43 ]. The change of cultivated land use type is closely related to human activities [ 63 ]. In recent years, ecological protection activities such as returning cultivated land to forest, returning cultivated land to grassland and returning cultivated land to lake in Hubei Province have changed agricultural production, so the change of cultivated land use may also be an important factor in the change of agricultural carbon emissions, but this paper does not consider it.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al (2017) explored the spatial and temporal heterogeneity of CO2 emissions in China's agricultural sector and its intensity, and used the Tapio decoupling model to examine the decoupling mechanism between agricultural economic growth and CO2 emissions in 30 Chinese provinces from 1997-2014, finding that CO2 emissions were severely decoupled from agricultural output for a longer period in eastern China. Wu et al (2019) decomposed the drivers of agricultural carbon emissions into four factors: energy mix, energy intensity, economic output, and population size based on the log-average divisor index (LMDI) approach, while Sui et al (2021) decomposed the drivers of agricultural carbon emissions into four factors: agricultural carbon intensity effect, structural effect, economic effect, and labor effect. Han et al (2018) used spatial autocorrelation analysis to explore the spatial correlation between China's agricultural carbon emission intensity and various indicators of the agricultural economy, and found that there is a positive spatial correlation between China's agricultural carbon emission intensity and agricultural GDP per unit arable area.…”
Section: Literature Reviewmentioning
confidence: 99%